Analisis Faktor Yang Berhubungan Dengan Ketidaklancaran Produksi Asi Pada Ibu Nifas Di Ruang Nifas Blud Rsu Provinsi Sulawesi Tenggara Tahun 2011 - Rahmawati Rahmawati (Jurnal Keperawatan, 2014)
According to WHO’s data, the coverage of exclusive breastmilk is still low for both develop and poor countries. One of the reasons of that condition is low breastmilk production of porturition woman. It reveals that the failure of giving breastmilk, particularly exclusive breastmilk is caused by breastmilk production deficiency since the first day of baby’s birth. Therefore, the baby is more often given prelactal food which is not good. This research investigated relationship of nutrient state, breast treatment, ANC Story, and IMD with breastmilk production deficiency. A cross sectional design study was conducted for 138 samples (samples were determined with simple random sampling method). There were two statistic test, those were bivariate statistic test by chi square and multivariate by logistic regression. The results showed that nutrient state (p = 0.000), breast treatment (p = 0.000), ANC Story (p = 0.000) and IMD (p = 0.000) had a relationship to breastmilk production deficiency. It was obtained from logistic regression test that IMD was the most influent factor involved in breastmilk production deficiency (wald 23.670; p = 0.000). Those results indicate that counseling training program for midwife about giving breastmilk need to be increased and IMD implementation acquire to be optimized. It is also important to increase elucidation and socialization about the importance of giving exclusive breastmilk everytime the pregnant woman doing checkup. Key words : Breastmilk production deficiency, IMD